The Occupational Health Nursing Education Components Most Influenced by Informatics Technology Based on Gamification and Fogg's Models: a Case Study in Indonesia - Isak Jurun Hans Tukayo; Mohammad Saljan; I Ketut Swastika; Syaifoel Hardy (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2021)
The rapid development of informatics technology (IT) in healthcare in the digital era has not been in line with the development of industrial nursing informatics education in Indonesia. The discrepancy is disturbing the operational activities of nursing clinicians who stand between the need of client, business, and the quality of services. The objective is to explore the benefit to the largest components of education that have changed due to IT interventions. This research used the Case Study method. The instrument was a case management version of the American Board of Occupational Health Nursing (ABOHN). The purposive sampling population was 350 nurses and nursing students who filled a questionnaire based on the Likert Scale, focused on the influence of IT on OHN education. The supporting data was from 15 major campuses in Indonesia that have nursing majors and IT departments, also from ABOHN and other OHN international bodies. The data was processed by the Statistical Package for Social Sciences (SPSS) 25 version, in the table of Pearson Correlation. Gamification and Fogg's Behavior models were used to identify the influence of IT on OHN education. The data analysis showed a significant impact of IT on OHN education with a value of 0.782. The Influence of IT towards OHN learning materials based on Gamification and Fogg’s Models also showed of 9 OHN competency categories (100%), indicating the need for IT support was absolute. Case management result projected that the application of Gamification with Fogg's model with the application of IT on the OHN education proved the magnitude influence of IT on 8 components, i.e.: teaching methods, learning materials, learning methods, students’ learning interests, campus facilities, lecturer’s competencies, campus management, and the education curriculum. The IT intervention will simplify the OHN education system, provide more effective, and efficient OH nursing practice in the workplace.